Effect of informative seminars during national acne week on participants' knowledge about acne in Turkey - Hatice Kaya Özden; Kamer Gündüz; Hamdi Özcan; Aysun Şikar Aktürk; Filiz Topaloğlu Demir; Tuğba Özkök Akbulut; Ayşe Serap Karadağ (Galenos Publishing House, 2021)
Background and Design: To investigate the contribution of informative presentations about acne vulgaris and questionnaires administered before and after informative meetings on patients' awareness and consciousness. Materials and Methods: Participants were asked to fill out a 20-question survey before and after informative seminars in hospitals and secondary and high schools as part of National Acne Week. The level of statistical significance was set as p≤0.05. Results: A total of 466 participants completed the survey before and after the seminar, and the mean age of the participants was 17.4±6.9. Before the seminar, 31.1% of participants thought that acne is originated from the liver, whereas this figure decreased to 16.7% after the seminar. In all, 47.6% of participants consulted doctors and 23.9% consulted social media to seek information about acne; however, after receiving training, 77% preferred to consult a doctor. Of the participants, 51.1% were expecting to see the results of acne treatment in 1 or 2 weeks, whereas 83.3% stated that the effects would be seen in 2 or 3 months after the seminar. When the participants' educational background was grouped as "secondary-high school-other," a statistically significant difference was obtained (p<0.05). Conclusion: Our study features both patients' misconceptions and their incorrect attitudes about acne, and their level of knowledge improved significantly as a result of educational seminars. The relative benefit derived from educational seminars was positively related to the participants' highest level of education.